PUBLIC AFFAIRS. MANAGEMENT PLAN PROGRESS REPORT. (Tufts Archival Research Center, 2007)
Marginalia; Memo from Peter Sparber to William Kloepfer with attached Management Plan Progress Report. Addresses in detail topics including: media relations, excise tax increases, the accidental fire issue and the public smoking issue. Details special projects and production services and lists all current projects.